“Unconscious Christianity” And The “Anonymous Christian” in The Theology of Dietrich Bonhoeffer And Karl Rahner - Kelly, Geffrey B. (Philosophy & theology, 1995)
The struggle that prompted Bonhoeffer’s “unconscious Christianity” offers a concrete illustration of the commonsensical in Rahner’s “anonymous Christian.” Thus Rahner’s theory adds theological coherence to what Bonhoeffer intuited. While Bonhoeffer faced the seeming ineffectiveness of Jesus’ teaching for the majority of Christians in Germany, Rahner faced his church’s view of Augustine’s “massa damnata” through a reexamination of church mission and theological categories. In both theologians, Jesus the God-man is the symbol of God’s communion with “the human” in God’s care for all peoples. The article concludes by asking whether the advent of such Christologies signals an approaching time of greater humility with regard to the Christian path to salvation.